Case Report: Cedecea lapagei Infection: Report of a Case in Peru and Review of the Literature - Al-Kassab-Cordova, Ali (2023)
Cedecea lapagei is a gram-negative, non-encapsulated, facultative anaerobic bacterium that has been reported in only a few cases with varying clinical presentations, drug susceptibility, and treatment since its first isolation in 1981. This study aimed to describe a case report of C. lapagei in Peru and systematically review the documented case reports of individuals infected with C. lapagei. A 59-year-old man who had become bedridden with Parkinson’s disease and had epilepsy presented with a 1-week history of fever and sore throat and was admitted. Physical examination revealed an obtundation state and abolished vesicular murmur in the right hemithorax. During hospitalization, the patient was diagnosed with various infections, including tuberculosis, for which he received broad-spectrum antibiotics. In the absence of clinical improvement, a urine culture was performed showing C. lapagei (detected by BD Phoenix M50 system, Vernon Hills, IL). The patient received amoxicillin/clavulanate and was discharged. Case reports of C. lapagei were also searched in five databases on January 28, 2023. Twenty cases of C. lapagei were reported worldwide between 2006 and 2022, 16 of which involved adults. Fever was the most common manifestation (75%), and pneumonia was the primary form of presentation (45%). Moreover, 90% of the patients had at least one comorbidity, and 15% died. Also, most of the isolates were sensitive to ciprofloxacin (81%), meropenem (62%), and amikacin (60%). Overall, C. lapagei should be suspected in compromised hosts, particularly those with pneumonia. Although the bacterium can affect various organs and the antibiotic susceptibility pattern is variable, quinolones, tetracyclines, and carbapenems seem to be the first therapeutic option.